I repropose a question I have had no answer on
I am trying to calculate $∇_wMSE=0$ and $∇_mMSE=0$ with '$w$' and '$m$' being matrices of unknown parameters and $MSE=(X⋅m⋅w−Y)^2$ ($X$ and $Y$ are matrices of known values).
If I simply had one set of parameters, i.e., $∇_wMSE=0→∇_m(X⋅m−Y)^2=0$, the solution would be $m=(X^T⋅X)−1⋅X^T⋅Y$
With the two sets of parameters: $∇_wMSE=0→∇_w(X⋅m⋅w−Y)^2=0$
How to solve this last equation? I could apply the chain rule, multiplying by $∇_mX⋅m$, but I am not sure how to then multiply the equation by this result.